Integrating network pharmacology and in vivo model to reveal the cardiovascular protective effects of kaempferol-3-O-rutinoside on heart failure - Guo Lu-Qin; Zhou Lan; Li Sheng-Nan; Bai Juan; Shi Ling-Li; Hua Fang; Zhou Peng (Acta Pharmaceutica)
Kaempferol-3-O-rutinoside (KR) has an excellent cardioprotective effect, but its mechanism of action is not clear. Network pharmacology was used to predict the signaling pathways, whereas molecular docking was used for preliminary validation of KR binding to targets. AMI model rats with ligated left anterior descending coronary arteries were established. HE staining was used to detect pathological changes, and ELISA was used to detect the expression of TNF-α and IL-6. Network pharmacology results showed PI3K-AKT signaling pathway may be the main mechanism, and molecular docking predicted that KR could bind strongly to the PI3K and AKT. KR could significantly reduce cardiac pathological changes, decrease the level of TNF-α and IL-6, and enhance the mRNA and protein expressions of PI3K and AKT. KR ameliorates HF after AMI by enhancing the expressions of PI3K and AKT, which will be helpful in elucidating the mechanism of KR through multiple techniques.